Formulasi Teologi Keluarga sebagai Model Preventif Dekadensi Moral Remaja di Era Digital melalui Pendekatan Interdisipliner - Novianti, Rizka; Arifianto, Yonatan Alex; Pantow, Frangky (KARDIA: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract: The development of digital technology has brought about major changes in human life, especially for adolescents who are searching for their identity. Easy access to information and unlimited interaction provide positive opportunities, but also trigger moral decadence such as bullying, pornography, promiscuity, drugs, and even crime. This condition signals a crisis of character and a weakening of moral values, which should be the foundation for adolescent development. This study aims to formulate family theology as a preventive model in dealing with moral decadence among adolescents in the digital age. The method used is descriptive qualitative with a literature study. Based on the theological foundation of the family as a divine institution, it is necessary to analyze the increasingly worrying phenomenon of moral decadence among adolescents in the digital age. To address this, an interdisciplinary approach to character education is needed so that youth development is not only spiritual but also in tune with the dynamics of modern life. All of this leads to the application of a practical model of family theology as a preventive strategy, in which the family functions as a center for moral and spiritual formation that is alive and able to guide adolescents in facing the challenges of the digital age. The results of the study show that, from a theological perspective, the family is a divine institution that functions as a center for faith, moral, and spiritual education. The formulation of family theology is realized through healthy parent-child communication, exemplary living, wise management of digital media, and shared spiritual practices. The integration of theology, psychology, sociology, and technology produces a comprehensive and relevant moral guidance strategy. Abstrak: Perkembangan teknologi digital membawa perubahan besar dalam kehidupan manusia, khususnya remaja yang sedang mencari jati diri. Akses informasi yang mudah dan interaksi tanpa batas memberi peluang positif, namun juga memicu dekadensi moral seperti perundungan, pornografi, perilaku seksual bebas, narkoba, hingga kriminalitas. Kondisi ini menandakan krisis karakter dan melemahnya nilai moral yang semestinya menjadi fondasi perkembangan remaja. Penelitian ini bertujuan merumuskan teologi keluarga sebagai model preventif dalam menghadapi dekadensi moral remaja di era digital. Metode yang digunakan adalah kualitatif deskriptif dengan studi pustaka. Berdasarkan landasan teologis keluarga sebagai institusi ilahi, perlu dilakukan analisis terhadap fenomena dekadensi moral remaja di era digital yang kian mengkhawatirkan. Untuk menghadapi hal ini, dibutuhkan integrasi pendekatan interdisipliner dalam pendidikan karakter, agar pembinaan remaja tidak hanya bersifat rohani, tetapi juga selaras dengan dinamika kehidupan modern. Semua ini mengarah pada penerapan model praktis teologi keluarga sebagai strategi pencegahan, di mana keluarga berfungsi sebagai pusat pembentukan moral dan spiritual yang hidup serta mampu menuntun remaja menghadapi tantangan di era digital. Hasil penelitian menunjukkan bahwa keluarga, dalam perspektif teologi, merupakan institusi ilahi yang berfungsi sebagai pusat pendidikan iman, moral, dan spiritual. Formulasi teologi keluarga diwujudkan melalui komunikasi sehat orang tua–anak, keteladanan hidup, pengelolaan media digital yang bijak, dan pembiasaan spiritual bersama. Integrasi disiplin teologi, psikologi, sosiologi, dan teknologi menghasilkan strategi pembinaan moral yang menyeluruh dan relevan.